Effect of cyclical forces on orthodontic tooth movement, from animals to humans. (June 2017) - Uribe, F.; Dutra, E.; Chandhoke, T.
Abstract: Vibration as a non‐invasive method is currently available for clinical use with the potential to accelerate the rate of tooth movement in orthodontics. The aim of this review was to evaluate the basic science and clinical literature on the effects of vibration on the axial and appendicular skeleton including the craniofacial bone. Vibration as a dynamic load consisting of high oscillatory forces of low magnitude has shown osteogenic and anti‐catabolic effects on bone. These effects have been observed in the craniofacial skeleton including the alveolar bone as increases in sutural width and alveolar bone formation. Animal studies have shown conflicting results on vibration when superposed to orthodontic tooth movement. The effects range from increasing to decreasing the rate of tooth movement. Clinical studies in accelerating the rate of tooth movement have similar findings observed in animal studies. High‐frequency oscillatory forces of low magnitude are able to affect bone formation and remodelling. These effects of vibration are primarily anabolic and anti‐catabolic in bone, including the craniofacial skeleton and alveolar bone. The effect of vibration on accelerating the rate of orthodontic tooth movement is contradictory. Higher levels of evidence studies have not been able to show an acceleratory effect.